Cyber spying tracking your family's (sometimes) secret online lives - Fair, Ted.; Nordfelt, Michael; Ring, Sandra; Cole, Eric. (Rockland, MA : Syngress Pub., 2005)
This book shows everyday computer users how to become cyber-sleuths. It takes readers through the many different issues involved in spying on someone online. It begins with an explanation of reasons and ethics, covers the psychology of spying, describes computer and network basics, and takes readers step-by-step through many common online activities, and shows what can be done to compromise them. The book's final section describes personal privacy and counter-spy techniques. By teaching by both theory and example this book empowers readers to take charge of their computers and feel confident they can be aware of the different online activities their families engage in. Expert authors have worked at Fortune 500 companies, NASA, CIA, NSA and all reside now at Sytex, one of the largest government providers of IT services. *Targets an area that is not addressed by other books: black hat techniques for computer security at the personal computer level. *Targets a wide audience: personal computer users, specifically those interested in the online activities of their families.
Why spy? -- Spying basics -- Technology overview : computer basics -- Network basics -- Taking control -- Spying on the PC -- Spying on Web browsing -- Spying on e-mail -- Spying on chat and instant messages -- Advanced techniques -- Counterspy : are you being watched?
Includes bibliographical references and index.
Keywords: Computer security; Internet; Electronic books